(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study explores the contribution of exercise in the development of fibromyalgia and is comprised of 120 publications discovered by search engines such as Pubmed, Google Scholar, and Ebsco Cinahl. Specific guidelines have been devised to ensure that the articles chosen are coincidental and of high quality, and which will serve as a guide in this study. There is some information that aims to give medical practitioners with updates on the significance of exercise to fibromyalgia disease, where the information provided is up to date and may be used as a reference. Fibromylagia affects around 10 million Americans, accounting for 3% to 6% of the worldwide population. The origins and history of the condition are addressed, as well as how patients cope with it on a daily basis. The advantages of an active lifestyle and the drawbacks of a sedentary lifestyle are very well understood. Lack of exercise, on the other hand, is associated with changes in contemporary cultures that have diminished the physical aspect of daily tasks. An exercise plan for fibromyalgia patients is presented in this article.